PENERAPAN MODEL STAD DENGAN MEDIA EKONQUIZZ SEBAGAI UPAYA MENINGKATKAN PEMAHAMAN KONSEP SISWA SD - Itsna Aryani, Hilmi; Dwi Ardianti, Sekar; Masfuah, Siti (LPPM STAI Muhammadiyah Probolinggo, 2024)
The aim of this research is to analyze the increase in students' conceptual understanding after implementing the STAD learning model combined with EkonQuizz media. This research was conducted at SDN Tamansari 03 which is located in West Kereppare hamlet, Pati Regency. The population in the study were all fourth grade students at SDN Tamansari 03 using a saturated sampling technique. The total population is 20 students consisting of 9 male students and 11 female students. This research uses a quantitative pre-experimental method combined with a One Group Pretest-posttest design. This research uses data collection techniques in the form of tests, interviews and documentation. Data analysis in this study used the N-Gain test. The research results show that there is an increase in students' understanding of concepts as seen from the results of the N-Gain test which shows significant changes. The N-Gain value is 0.6017 with a percentage of 60.17% indicating the category is quite effective. The use of the STAD model in combination with EkonQuizz media can also increase students' understanding of concepts, this can be seen from the results of the N-Gain test on each indicator which has experienced a significant increase. Based on the description above, it can be concluded that applying the STAD model combined with EkonQuizz media can improve students' understanding of concepts.